Sosialisasi Biodigester Sederhana dan Pengolahan Limbah Organik menjadi Biogas pada Siswa-Siswi SMK Muhammadiyah Bontang - Fitria Fitria; Mimin Septiani; Zakiyah Darajat (Jurnal Pengabdian Ahmad Yani, 2022)
Abstract Energy scarcity is a hot issue, which encourages the drafting team of Community Service Activities to socialize the use of organic waste into bioenergy on a simple scale. One example of the results of organic waste treatment is Biogas (Mayasari et al., 2010). The approach method used is to provide students with an understanding of the potential of renewable energy in the city of Bontang. Continuing by socializing the manufacture of simple reactors and the process of fermenting organic waste to produce biogas. From the results of this training, it can be concluded with enthusiasm from the students that the activities are carried out well and are able to increase students' knowledge about the potential waste in the surrounding environment and it is hoped that they will be able to practice making organic waste biodigesters on a simple scale. Keywords: Biodigester, Organic Waste, Smk Students